Inflammation of the Eye in Systemic Inflammatory Disorders: Keratitis. - Bachmann, B.; Jacobi, Christina; Cursiefen, C. (Klinische Monatsblätter für Augenheilkunde, 2011)
Systemic inflammatory diseases are associated with keratitis. In addition to the much less frequently occurring non-ulcerative keratitis, ulcerative inflammation of the corneal periphery is common in systemic inflammatory diseases. Significant systemic inflammatory diseases in this context are autoimmune connective tissue diseases (including rheumatoid arthritis, systemic lupus erythematosus or primary vasculitides such as polyarteritis nodosa or Wegener's granulomatosis), systemic autoimmune dermatological disorders (such as the cicatrising pemphigoid or Stevens-Johnson syndrome) and autoimmune diseases of the lacrimal system (such as the lacrimal gland involvement in primary Sjogren's syndrome or in graft-versus-host disease). In severe cases of peripheral ulcerative keratitis intensive topical therapy is initially combined with a systemic high-dose steroid therapy. In further progressing ulceration, surgery may help to preserve or restore the integrity of the eye and may suppress the autoimmune response by shielding the corneal antigens from blood and the lymphatic system. Systemic immune modulating therapy has to be done in close consultation with the rheumatologist.
EVALuna2:21024